EDUCATIONAL CRISIS MANAGEMENT: SCHOOL LEADERSHIP STRATEGIES DURING THE COVID-19 PANDEMIC - Ravit, Amir (E-Journal VFU, 2025)
The article shed lights on the COVID-19 that exposed significant vulnerabilities in education systems worldwide, particularly in countries lacking coordinated national strategies. It is mainly focused on the Israeli context, examining the ways used by the school principals to overcome the absence of comprehensive governmental guidance and to exercise critical leadership roles in managing the educational procwess. Through the lens of crisis management and educational leadership theory, the study analyses the challenges principals faced—including resource shortages, student disengagement, and emotional distress—and highlights their adaptive strategies in maintaining learning continuity and social support. The article concludes with policy recommendations aimed at strengthening school-based crisis preparedness and empowering educational leaders for future disruptions.